Analysis of Types of Sentences Based on Forms and Meanings in the Short Story Rembulan in the Eyes of Mother by Asma Nadia - Nurul Jumrah; Asih Kusumawati; Khanifa Kinanthi Aulina; Asep Purwo Yudi Utomo (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
A literary work does not only consist of one sentence, but there are many types of sentences that can be analyzed. Therefore, the researcher is interested in bringing up a literary work in the form of the short story "Remoon in the Eyes of Mother" by Asma Nadia, which contains several sentences that really support the research topic. This study aims to analyze the types of sentences based on form and meaning in Asma Nadia's short story "Remoon in Mother's Eyes". The research method used is a qualitative research method. The research data was obtained directly from the quotations contained in the short story "The Moon in the Eyes of the Mother" by Asma Nadia. The researcher took excerpts from short stories according to the things that will be discussed in this study, namely regarding the types of sentences. The types of sentences that will be discussed in this study are types of sentences based on form and meaning. Based on the form consists of 2 types, namely single sentences and compound sentences. Meanwhile, based on meaning, there are 3 types, namely declarative sentences, questions (interrogative), and commands (imperative). Through this research, it is hoped that readers can gain insight into knowledge about the types of sentences based on the forms and meanings contained in the short story "Rembulan di Mata Ibu" by Asma Nadia.